The Effects of Sex-Type, the Sex of the Avatar, and Salience of the Sex of the Avatar on Emotional Valence and Arousal - Prettyman, Duncan V.; Bolls, Paul D. (Frontiers in Psychology, 2021)
The objective of this study was to investigate the effects of avatar sex, salience of avatar sex, and player gender on less conscious embodied emotional arousal and valence versus consciously perceived emotional arousal and valence elicited by a gaming experience. The experiment conducted a 2 avatar sex (female x male) X 2 salience of avatar sex (high x low) X 2 player gender (sex-typed x non-sex-typed) mixed model factorial design. Participants were randomly assigned to one of two gameplay conditions (high-salience male and female avatar or low-salience male and female avatar) and then played two 15-minute sessions of a video game—one session playing the game as a male avatar and one session playing the game as a female avatar. The order in which participants played as either a male or female avatar was randomized. Psychophysiological indicators of arousal (skin conductance) and valence (facial electromyography) were recorded during gameplay. Self-report measures of arousal and valence were obtained immediately after each 15-minute session of gameplay. Data analysis tested hypotheses concerning the effects of avatar sex, salience of avatar sex, and player gender separately on real-time embodied variation in arousal and valence as revealed through physiological indicators and conscious perception of arousal and valence obtained through self-report measures.